Javanese Muslim with Diabetes in Yogyakarta Managing The Daily Self-Care Activity - Iman Permana; Muflikh Try Harbiyan (Intelektual Pustaka Media Utama, 2015)
Self-care, capability in performing certain activity in maintaining well-being in daily life, was regarded important especially among people with long-term condition such as diabetes. Locus of control and self-efficacy are among the self-agency factors that might influence how people engage with daily self-care activity in diabetes management. While, Javanese and Islamic values and norms are other parts of structure that support the effort. This study aimed to seek further into the experiences and perceptions among the Javanese Muslim on how they managed to do self-care in diabetes management. The study was done utilizing a mixed method approach with the usage of the Summary of Diabetes Self-care Activity (SDSCA) questionnaire to measure the level of self-care and followed by further interview to dig deeper into the perception and experiences and what are the opportunity or obstacle in performing daily self-care. A convenient sample of 100 participants has filled the questionnaires, with further 24 interviews. The study identified the moderate self-care practices as a separate notion, instead of an integrated and comprehensive concept amid the unavailability of a structured education program. Five themes were generated from the interviews, those are: education and knowledge, being in or out of control, Javanese way – sensitivity and surrender, peace of mind and role of Allah or God, and poor access to health care.